Health care utilisation by bullying victims: a cross-sectional study of a 9-year-old cohort in Ireland - Nixon, Elizabeth; Hayes, Catherine; Kelly, Dervla; Taut, Cristina; Zgaga, Lina; Williams, James; O'Dowd, Thomas; Reulbach, Udo (My University, 2018)
Children frequently refrain from disclosing being bullied. Early identification of bullying by healthcare professionals in children may prevent adverse health consequences. The aim of our study was to determine whether Health Care Utilisation (HCU) is higher in 9-year-olds who report being bullied and factors influencing type of HCU. The study consists of cross-sectional surveys of Child Cohort of Irish National Longitudinal Study of Children (Wave 1), 8,568 9-year-olds, and their carers. Being bullied was assessed by a self-reported questionnaire completed by children at home. HCU outcomes consisted of the following: visits to GP, Mental Health Practitioner (MHP), Emergency Department (ED), and nights in hospital by parent interview. Bivariate logistic regression and gender-stratified Poisson models were used to determine association. Victimisation by bullying independently increased visits to GP (OR 1.13, 95% confidence interval (CI): 1.03 to 1.25; p = 0.02), MHP (OR 1.31, 95% CI: 1.05 to 1.63; p = 0.02), though not ED visits (OR 0.99, 95% CI: 0.87 to 1.13; p = 0.8) or nights in hospital (OR 1.07 95% CI: 0.97 to 1.18; p = 0.2), adjusting for underlying chronic condition(s) and socio-demographic confounders. Victimised girls made higher GP visits (RR 1.14, 95% CI: 1.06 to 1.23; p < 0.001) and spent more nights in hospital (RR 1.10, 95% CI: 1.04 to 1.15; p < 0.001). Victimised boys were more likely to contact MHPs (RR 1.21, 95% CI: 1.02 to 1.44; p = 0.03). 9-year-old bullied subjects were more likely to utilise primary care services than non-bullied 9-year-olds. Different HCU patterns were observed according to gender and gender differences in the presentation of victimisation. Our findings may lead to the development of clinical practice guidelines for early detection and appropriate management of bullied children.
PUBLISHED
Keywords: Bullying; Gender; Primary health care; General practice; Health care utilisation; Mental health